(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa: le tappe di un leading case controverso - 2. La presenza dei musulmani in Tracia: un itinerario storico tra fonti interne e internazionali - 3. Il quadro normativo vigente al momento della causa - 4. La Corte e il suo legal reasoning tra equità e uguaglianza - 5. Conclusione: il soft law come substrato valoriale di una decisione annunciata. The Muslims of Thrace and the case Molla Sali c. Greece. A historical and legal itinerary between religious pluralism and demands for equality ABSTRACT – The article is inspired by the Molla Sali v. Greece case, resolved by the ECHR. Starting from this case, the article analyzes the complex historical development of the legislation relating to the Muslim minority in the Greek region of Thrace. In particular, the article deals with the prerogatives of the mufti in the judicial field and the application of Islamic law to relations among private individuals. In addition to the treaties concluded between the decaying Ottoman Empire and the main European powers, the article explores the corresponding implementing rules in the Greek legal system. Finally, the article proposes some critical considerations about balancing the principle of equality and the rights of minorities.